Vordis, Veradartcir Tun . Son, Get Back Home - Ohanyan, Mariam (Galstyan, Irina, 2007)
Verzio FF submission The film is about the dramatic predicament of Dr. Valentina Safrazbekian. During the 1930's reprisals she lost her father and became the daughter of "the people's enemy," however she succeeded in obtaining education, rose to her feet, defended her candidate thesis, and taught at a college; during the crisis and cold of the 1990s she defended her doctoral thesis. However, her son went abroad to earn money. Her health was underminned and her only desire to see her son before her death never materialized.